Evaluasi penerapan pajak penghasilan atas bisnis sewa ruangan pada kantor pengelola Star Square Manado - Mokodompit, Jelita Astrid; Afandi, Dhullo; Weku, Priscillia (Riset Akuntansi dan Portofolio Investasi, 2025)
Tax is a fundamental element of a country's financial system and plays a crucial role in the economy. Income Tax Article 4 Paragraph 2 is a significant tax for business activities, especially in the room rental business. Imposing income tax on the room rental business poses challenges, primarily in understanding and interpreting the applicable tax regulations to fulfil obligations and comply with taxation rules. This study evaluates the application of tax on the Room Rental Service Business at the Star Square Manado Management Office using a descriptive qualitative method. The results show that Star Square Manado has implemented tax regulations in accordance with applicable government regulations and has recorded accounting for every transaction that occurs.